THE EFFECTIVENESS OF THE MODEL OF THE PRE-COMPETITIVE STAGE OF TRAINING HIGHLY QUALIFIED GOALKEEPERS IN BEACH SOCCER - Mukhamedzyanov, R.R.; Nifontov, M.Yu.; Privalov, A.V.; Roop, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to theoretically develop, experimentally substantiate and evaluate the effectiveness of the model of the pre-competitive stage of training highly qualified goalkeepers in beach soccer. Methods and structure of the study. The experiment was carried out for three years from 2018-2021 on the basis of professional beach soccer clubs participating in the Super League and the First Division of the Russian Championship. The scientific study included four stages. The solution of the tasks set was carried out in the process of explanatory research, in which 24 highly qualified beach soccer goalkeepers with qualifications from Candidate Master of Sports to International Master of Sports of Russia took part. Results and conclusions. The presented data give grounds to assert that the model of the pre-competitive stage of training highly qualified goalkeepers in beach football, developed and implemented in the annual cycle, which includes target, content, procedural and control modules for optimizing the content of training sessions and pre-game warm-up, can significantly improve the qualitative and quantitative characteristics of game actions and as a result, the level of sportsmanship.